Plasma spraying ceramic powder, ceramic composite coating and preparation method thereof

By reasonably proportioning nano YSZ powder and silicate glass powder and combining with sealing agent, the pore problem of atmospheric plasma sprayed ceramic coating in corrosion environment is solved, and the density and corrosion resistance of the coating are significantly improved. , extends its service life.

CN119118634AActive Publication Date: 2024-12-13PUTIAN (CHANGZHOU) SURFACE COATING TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411211048.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

Atmospheric plasma sprayed ceramic coatings are prone to pores or cracks in corrosive environments, causing corrosive media to penetrate, reducing the service life of the coating and limiting its application in the corrosion-resistant industry.

Method used

Using reasonable ratio of nano YSZ powder and silicate glass powder, high-temperature sintering and mechanical ball milling treatment, the porosity of the coating is reduced, the density is improved, and the sealing agent is used during the spraying process to further enhance the coating. Density and corrosion resistance.

Benefits of technology

It significantly reduces the porosity of the ceramic composite coating, improves its density and corrosion resistance, extends the service life of the coating, and maintains good corrosion resistance under high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005020321880000101
    Figure BDA0005020321880000101
  • Figure BDA0005020321880000111
    Figure BDA0005020321880000111
Patent Text Reader

Abstract

The invention relates to the field of thermal spraying ceramic coatings, and particularly discloses plasma spraying ceramic powder, a ceramic composite coating and a preparation method of the ceramic composite coating. The plasma spraying ceramic powder is prepared from the following raw materials in parts by weight: 100 parts of nano powder and 10 to 30 parts of silicate glass powder, the nano powder comprises nano Al2O3 powder, nano TiO2 powder, nano CeO2 powder and nano YSZ (Yttria Stabilized Zirconia) powder in a weight ratio of (80-86): 10: 2: (2-8). The plasma spraying ceramic powder has the beneficial effects of being good in fluidity, smooth in surface, high in compactness and good in sphericity degree, and the prepared ceramic composite coating has the beneficial effects of being low in porosity, high in compactness, good in corrosion resistance and long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of thermal spraying ceramic coatings, and more specifically, to a plasma spraying ceramic powder, a ceramic composite coating and a preparation method thereof. Background Art

[0002] With the continuous development of cutting-edge technologies in the fields of aerospace, energy and electricity, national defense and military industry, the use requirements of large equipment and key components involved are becoming more stringent. Therefore, how to extend the service life of related structural materials under extreme conditions such as high temperature and strong corrosion has become one of the core issues that need to be solved urgently. Generally speaking, there are two ways to effectively solve this problem: one is to change the chemical composition, phase stability and organizational structure of the matrix material itself by various means, so as to improve the intrinsic performance of the matrix material, but this method has the limitations of long exploration cycle and high application cost; the other is to use surface treatment technology to enhance the protection of the matrix material. According to the use requirements of structural materials in different environments, corresponding antioxidant, high temperature resistant and corrosion resistant functional coatings are prepared, and the coatings are covered on the surface of the matrix material by physical or chemical means, so as to slow down the process of damage and failure from the surface of the material to its interior, and finally achieve the purpose of extending the service life of the material. Compared with the matrix modification method, surface modification has fewer limiting factors, a wider range of application and stronger pertinence. Therefore, this method has been applied in more and more scientific research and actual production processes and has achieved good results.

[0003] In the field of surface modification technology, it usually includes chemical vapor deposition technology (CVD), physical vapor deposition technology (PVD), thermal spraying technology, etc. Although the coating prepared by CVD has a higher density, the equipment cost investment is large and the operation is complicated, and the material and shape of the substrate are required to be high; the coating prepared by PVD has strong wear resistance, but the cost is still high; in comparison, the cost of thermal spraying technology is lower, the operation is more convenient, and the scope of application is wider. As one of the important thermal spraying technologies, plasma spraying technology has many advantages such as fast deposition speed, high work efficiency and flexible production methods. It is an important development direction in the field of thermal spraying. According to the different media and environments for generating plasma, plasma spraying technology can be divided into atmospheric plasma spraying, liquid precursor plasma spraying and supersonic plasma spraying.

[0004] Atmospheric plasma spraying (APS) is a process in which gases (such as argon, helium, nitrogen, etc.) are fed into the arc area of ​​a plasma spray gun. Under the action of high voltage and high current, the gas is ionized to form plasma. This plasma jet has the characteristics of high temperature and high speed. Under the action of the plasma jet, the powder material is heated to a high temperature and melted, and then splashed onto the surface of the substrate at a high speed to form a coating. Since this spraying process can be carried out at room temperature and does not require a vacuum environment, it is widely used in the fields of material protection, repair and improvement. However, the spraying process determines that there must be defects such as pores or cracks on the surface and inside of the coating formed, and these defects provide channels for the penetration of corrosive media. In a corrosive environment, the corrosive medium penetrates into the interface between the coating and the metal through the defects and microcracks of the ceramic layer and causes severe electrochemical corrosion, which leads to cracking and peeling of the coating, reducing the service life of the coating in a corrosive environment and limiting the application of atmospheric plasma sprayed ceramic coatings in the corrosion-resistant industry. Summary of the invention

[0005] In order to reduce the porosity of the ceramic composite coating, improve the density of the ceramic composite coating, and thus extend the service life of the ceramic composite coating, the present application provides a plasma sprayed ceramic powder, a ceramic composite coating, and a preparation method thereof.

[0006] In the first aspect, the present application provides a plasma spraying ceramic powder, which adopts the following technical solution: A plasma spraying ceramic powder, the raw materials used include the following components in parts by weight: 100 parts of nano powder and 10-30 parts of silicate glass powder; the nano powder includes nano Al2O3 powder, nano TiO2 powder, nano CeO2 powder and nano YSZ powder in a weight ratio of (80-86):10:2:(2-8).

[0007] By adopting the above technical solution, the Y in the nano YSZ (yttria partially stabilized zirconia) powder of the present application is 3+ At higher temperatures, it can diffuse into ZrO2 to maintain the stability of the ZrO2 phase, while ZrO2 is easily enriched at the Al2O3 grain boundaries to refine the Al2O3 grains and disperse them. In addition, Y2O3 helps to improve the wetting properties of the Al2O3 mixed powder and reduce the melting point of the mixed powder, so that the mixed powder can be fully melted during the heating process and fill the interlayer gaps combined with the capillary action between the nanoparticles. At the same time, Y2O3 will hinder the migration of other ions, reduce the grain boundary migration rate and inhibit grain growth, thereby reducing the porosity of the coating, improving the density of the coating, and extending the service life of the ceramic composite coating.

[0008] However, ZrO2 has the characteristic of low thermal conductivity. If too much nano-YSZ powder is added, it will affect the full melting and spreading of the mixed powder, and it is easy to produce pores. In addition, the grains merge and grow rapidly at high temperatures, and when they hit the substrate, they cool down and condense rapidly at the interface, shrinking sharply and separating. The uneven heating of the powder causes some powder particles to accumulate in the coating before they are completely melted, which will also cause an increase in pores. Therefore, this application optimizes the addition amount of nano-YSZ powder, so that the coating has a lower porosity.

[0009] In addition, the present application also mixes nano powder and silicate glass powder in a certain proportion. Silicate glass powder has the characteristics of low viscosity and good fluidity at high temperature. During the spraying process, the molten droplets quickly solidify after hitting the surface of the substrate, which plays a bonding role. It can also better fill the pores between the nano powder droplets, increase the area of ​​​​droplet spreading, and form a large layer spread, thereby reducing the porosity and increasing the density of the coating. However, the amount of silicate glass powder added should not be too high. If the amount added is too large, the brittle glass material will cause stress concentration when the plasma spray is quickly cooled, thereby generating cracks and increasing the porosity.

[0010] Preferably, the nano powder includes nano Al2O3 powder, nano TiO2 powder, nano CeO2 powder and nano YSZ powder in a weight ratio of 82:10:2:6.

[0011] By adopting the above technical solution, the present application further optimizes the addition ratio of nano YSZ powder in the nano powder, thereby further reducing the porosity of the coating, improving the density of the coating, enhancing the corrosion resistance of the coating, and extending the service life of the coating.

[0012] Preferably, the average particle size of the plasma sprayed ceramic powder is 52.34-82.35 μm, the fluidity is 10.73-11.87 g / min, and the bulk density is 0.52-0.56 g / cm 3 , tap density is 0.87-0.90g / cm 3 .

[0013] By adopting the above technical solution, since the original nano powder has a small particle size, high chemical activity and strong adhesion, there is a spontaneous agglomeration phenomenon and the fluidity is extremely poor. It cannot be directly used for plasma spraying and needs to be processed to prepare it into a feed with good fluidity and can be used for plasma spraying. The present application mixes nano powder and silicate glass powder. After mechanical ball milling, the powder undergoes continuous agglomeration and tearing and then reorganizes into a slurry. In order to better disperse the nano powder, ammonium citrate can also be added as a dispersant. Then, it is spray granulated to form powder particles, and then high-temperature sintering is performed to make the powder more dense. Finally, a plasma spray ceramic powder with good fluidity, smooth surface, high density and good sphericity is obtained. The average particle size is 52.34-82.35μm, the fluidity is 10.73-11.87g / min, and the loose density is 0.52-0.56g / cm 3 , tap density is 0.87-0.90g / cm 3 .

[0014] In a second aspect, the present application provides a method for preparing a ceramic composite coating, which adopts the following technical solution: A method for preparing a ceramic composite coating comprises the following steps: S1. Degreasing and cleaning the substrate surface and pre-treating it by sandblasting; S2. Spraying a bonding layer on the surface of the substrate treated in step S1, and then spraying a plasma sprayed ceramic powder; S3. Use a sealing agent to seal the substrate treated in step S2 to obtain a ceramic composite coating.

[0015] By adopting the above technical solution, the present application first degreases and cleans the surface of the substrate, the substrate is Q355 steel, the size is φ25.4×8mm, the degreasing and cleaning process is: use a grinder to grind off the surface dirt, then wipe it with anhydrous ethanol, and then clean the oil stains by chamfering and acetone solution. Then perform sandblasting pretreatment to make the substrate surface have a certain degree of roughness and activity, which is beneficial to improve the bonding strength of the coating. The type of sand used for sandblasting pretreatment in the present application is white corundum sand with dense texture and high hardness, and the sand size is 0.68-0.82mm.

[0016] Due to the large difference in thermal expansion coefficients between the ceramic layer and the substrate, the residual stress in the coating will be too large, affecting the service life of the coating and causing thermal mismatch. In order to solve this problem, after sandblasting pretreatment, a bonding layer is first sprayed on the surface of the substrate as a primer, and then plasma sprayed ceramic powder is sprayed. This can achieve a transition from the difference in thermal expansion coefficients, reduce the residual stress inside the coating, and improve the durability and service life of the coating. The primer has good adhesion, can provide good coating adhesion, and improve the bonding strength of the overall coating. The primer of the present application is NiCrAlY, and the thickness of the primer is 90±10μm. The thickness of the ceramic layer formed by the plasma sprayed ceramic powder spraying of the present application is 200±20μm.

[0017] After the coating is formed by atmospheric plasma spraying, the present application further uses a sealing agent to post-treat the coating, which further reduces the porosity of the coating, enhances the density of the coating, reduces the possibility of particle shedding on the coating surface, overall peeling and failure of the coating, improves the corrosion resistance of the coating, and extends the service life of the coating.

[0018] Preferably, in step S1, the sandblasting pressure of the sandblasting pretreatment is 0.5-0.6 MPa, the sandblasting distance is 100-120 mm, and the sandblasting angle is 75-80°.

[0019] Preferably, in step S2, the gas flow rate during spraying is 30-40 L / min, the powder feeding rate is 10-20 g / min, the spraying distance is 100-120 mm, and the spraying angle is 30-90°.

[0020] Preferably, the gas includes Ar and H2, with Ar serving as the main gas and carrier gas and H2 serving as the auxiliary gas.

[0021] Preferably, the sealing agent in step S3 comprises an organosilicon base material and ZrO2-coated SiC-CeO2 sealing particles in a weight ratio of (1.8-2.2):1.

[0022] By adopting the above technical solution, the present application uses an organic silicon base material and ZrO2 coated SiC-CeO2 sealing particles to mix to form an inorganic-organic hybrid sealing agent, and then performs a sealing treatment on the coating, which greatly reduces the porosity of the coating, improves the corrosion resistance of the coating, and can be used for a long time in a high temperature environment. The organic silicon base material of the present application is SiO2 sol.

[0023] Preferably, the weight ratio of SiC and CeO2 in the ZrO2-coated SiC-CeO2 sealing particles is (98-99.5):(0.5-2).

[0024] By adopting the above-mentioned technical scheme, the present application firstly obtains SiC-CeO2 composite powder by ball milling a mixture of SiC and CeO2 in a certain ratio, utilizes CeO2 to reduce the high-temperature decomposition rate of SiC, and at the same time plays a role in stabilizing the ZrO2 phase in the nano YSZ powder, and then utilizes ZrO2 to coat the SiC-CeO2 composite powder, thereby realizing the effective combination between the sealing particles and the coating, and further enhancing the sealing effect of the sealing agent.

[0025] In a third aspect, the present application provides a ceramic composite coating produced by the above-mentioned preparation method.

[0026] In summary, this application has the following beneficial technical effects: 1. The average particle size of the plasma sprayed ceramic powder of this application is 52.34-82.35 μm, the fluidity is 10.73-11.87 g / min, and the bulk density is 0.52-0.56 g / cm 3 , tap density is 0.87-0.90g / cm 3 , with the characteristics of good fluidity, smooth surface, high density and good sphericity; 2. The ceramic composite coating of the present application has the characteristics of low porosity and high density, good corrosion resistance, and can serve for a long time at high temperature and has a long service life. DETAILED DESCRIPTION

[0027] The present application is further described in detail below with reference to the embodiments.

[0028] Unless otherwise specified, the raw materials used in this application are all commercially available products, including: Nano-Al2O3 powder, particle size is 10-20nm, purity is 99.5%; Nano-TiO2 powder, particle size is 10-50nm, purity is 99.9%; Nano CeO2 powder, particle size is 10-20nm, purity is 99.9%; Nano YSZ powder, 8wt% Y2O3-ZrO2 nano powder, particle size 10-30nm, purity 99.9%; Silicate glass powder, particle size 2-3μm, purity ≥99.45%, SiO2 content 7.5%, MgO content 3.881%, CaO content 8.127%, Fe2O3 content 0.0011%; The substrate is Q355 steel with a size of φ25.4×8mm; White corundum sand, sand particle size is 0.68-0.82mm; Tetraethyl orthosilicate, analytical grade, was purchased from Chengdu Kelong Chemical Co., Ltd.; SiC, analytical grade, particle size 10 μm, purchased from Chengdu Kelong Chemical Co., Ltd.; ZrOCl2·8H2O, analytical grade, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; CeO2, analytical grade, particle size 2 μm, purchased from Chengdu Kelong Chemicals Co., Ltd.; Polyvinyl butyral ester, analytical grade, was purchased from Chengdu Kelong Chemical Co., Ltd.; SiO2 sol was purchased from Dongguan Huihe Yongsheng Nanotechnology Co., Ltd., model S-1430, with an active ingredient content of 30%.

[0029] Preparation Example 1.1 Plasma sprayed ceramic powders are produced by the following method: a. At a speed of 300r / min, 1.72kg of nano-Al2O3 powder, 0.2kg of nano-TiO2 powder, 0.04kg of nano-CeO2 powder, 0.04kg of nano-YSZ powder and 0.2kg of silicate glass powder were put into a ball mill and milled for 24h to obtain a slurry, wherein the ball milling medium used zirconia ceramic balls with a diameter distribution of 3mm:5mm:10mm = 20%:30%:50%, and the ball-to-material ratio was 10:1; b. Place the slurry in a centrifugal spray dryer for spray drying at an inlet temperature of 220°C, an outlet temperature of 110°C, a nozzle speed of 180r / s, and a feed rate of 3L / h. Then, sieve the slurry through a 180-mesh sieve and then a 400-mesh sieve to obtain powder particles with a particle size of 15-90μm and an average particle size of 50±2μm. c. The powder particles were first heat treated at 200°C for 1 hour, then heated to 350°C at a heating rate of 5°C / min, heat treated for 1 hour, then heated to 600°C at a heating rate of 5°C / min, heat treated for 1 hour, and finally heated to 1150°C at a heating rate of 5°C / min, sintered at high temperature for 2 hours, and then cooled to obtain an average particle size of 58.41μm, a fluidity of 11.87g / min, and a bulk density of 0.52g / cm 3 , tap density is 0.90g / cm 3 Plasma sprayed ceramic powder.

[0030] Preparation Example 1.2 The difference from Preparation Example 1 is that in step a, the amount of nano-Al2O3 powder is 1.68 kg, the amount of nano-TiO2 powder is 0.2 kg, the amount of nano-CeO2 powder is 0.04 kg, and the amount of nano-YSZ powder is 0.08 kg. The average particle size of the plasma sprayed ceramic powder finally obtained in step c is 56.52 μm, the fluidity is 11.25 g / min, and the bulk density is 0.54 g / cm 3 , tap density is 0.87g / cm 3 , and the rest are the same as in Preparation Example 1.

[0031] Preparation Example 1.3 The difference from Preparation Example 1 is that in step a, the amount of nano-Al2O3 powder is 1.64 kg, the amount of nano-TiO2 powder is 0.2 kg, the amount of nano-CeO2 powder is 0.04 kg, and the amount of nano-YSZ powder is 0.12 kg. The average particle size of the plasma sprayed ceramic powder finally obtained in step c is 53.18 μm, the fluidity is 10.73 g / min, and the bulk density is 0.55 g / cm 3 , tap density is 0.87g / cm 3 , and the rest are the same as in Preparation Example 1.

[0032] Preparation Example 1.4 The difference from Preparation Example 1 is that in step a, the amount of nano-Al2O3 powder is 1.6 kg, the amount of nano-TiO2 powder is 0.2 kg, the amount of nano-CeO2 powder is 0.04 kg, and the amount of nano-YSZ powder is 0.16 kg. The average particle size of the plasma sprayed ceramic powder finally obtained in step c is 52.34 μm, the fluidity is 11.02 g / min, and the bulk density is 0.56 g / cm 3 , tap density is 0.89g / cm 3 , and the rest are the same as in Preparation Example 1.

[0033] Preparation Example 2.1 The difference from Preparation Example 1 is that in step a, the amount of silicate glass powder used is 0.4 kg, and the average particle size of the plasma sprayed ceramic powder finally obtained in step c is 57.63 μm, the fluidity is 11.42 g / min, and the bulk density is 0.53 g / cm 3 , tap density is 0.89g / cm 3 , and the rest are the same as in Preparation Example 1.

[0034] Preparation Example 2.2 The difference from Preparation Example 1 is that in step a, the amount of silicate glass powder used is 0.6 kg, and the average particle size of the plasma sprayed ceramic powder finally obtained in step c is 55.27 μm, the fluidity is 11.16 g / min, and the bulk density is 0.54 g / cm3 , tap density is 0.87g / cm 3 , and the rest are the same as in Preparation Example 1.

[0035] Comparative Preparation Example 1.1 The difference from Preparation Example 1 is that in step a, no nano YSZ powder is added, specifically, 1.76 kg of nano Al2O3 powder, 0.2 kg of nano TiO2 powder, and 0.04 kg of nano CeO2 powder are added. The average particle size of the plasma sprayed ceramic powder finally obtained in step c is 56.15 μm, the fluidity is 11.16 g / min, and the bulk density is 0.51 g / cm 3 , tap density is 0.91g / cm 3 , and the rest are the same as in Preparation Example 1.

[0036] Comparative Preparation Example 1.2 The difference from Preparation Example 1 is that in step a, the amount of nano-Al2O3 powder is 1.56 kg, the amount of nano-TiO2 powder is 0.2 kg, the amount of nano-CeO2 powder is 0.04 kg, and the amount of nano-YSZ powder is 0.2 kg. The average particle size of the plasma sprayed ceramic powder finally obtained in step c is 51.5 μm, the fluidity is 11.05 g / min, and the bulk density is 0.58 g / cm 3 , tap density is 0.87g / cm 3 , and the rest are the same as in Preparation Example 1.

[0037] Comparative Preparation Example 2.1 The difference from Preparation Example 1 is that in step a, no silicate glass powder is added, and the average particle size of the plasma sprayed ceramic powder finally obtained in step c is 56.15 μm, the fluidity is 11.16 g / min, and the bulk density is 0.51 g / cm 3 , tap density is 0.91g / cm 3 , and the rest are the same as in Preparation Example 1.

[0038] Comparative Preparation Example 2.2 The difference from Preparation Example 1 is that in step a, the amount of silicate glass powder added is 0.8 kg, and the average particle size of the plasma sprayed ceramic powder finally obtained in step c is 51.85 μm, the fluidity is 11.02 g / min, and the bulk density is 0.57 g / cm 3 , tap density is 0.88g / cm 3 , and the rest are the same as in Preparation Example 1.

[0039] Preparation Example 3.1 The sealing agent is prepared by the following method: I. SiC, CeO2 and polyvinyl butyral ester with a weight ratio of 98:2:1 were added to a ball mill and ball-milled for 4 hours to obtain a mixed slurry, and then the mixed slurry was dried, debonded and ground in sequence to obtain a SiC-CeO2 composite powder with a particle size of less than 5 μm; II. The SiC-CeO2 composite powder was completely dispersed in an aqueous solution of ZrOCl2·8H2O, and then the pH value was adjusted with hydrochloric acid, and then dried, calcined, and ground to obtain ZrO2-coated SiC-CeO2 sealing particles; III. Mixing SiO2 sol with ZrO2-coated SiC-CeO2 sealing particles in a weight ratio of 1.8:1 to obtain a sealing agent.

[0040] Preparation Example 3.2 The difference from Preparation Example 3.1 is that the weight ratio of SiC and CeO2 is 99.5:0.5, and the rest is the same as Preparation Example 3.1.

[0041] Preparation Example 3.3 The difference from Preparation Example 3.1 is that the weight ratio of SiO2 sol to ZrO2 coated SiC-CeO2 sealing particles is 2.2:1, and the rest is the same as Preparation Example 3.1.

[0042] Example 1.1 A method for preparing a ceramic composite coating comprises the following steps: S1. Use a grinding wheel to grind away dirt on the surface of the substrate, then wipe it with anhydrous ethanol and chamfer the edge area of ​​the substrate by 0.5 mm, then completely immerse the substrate in an acetone solution for ultrasonic cleaning for 10 minutes to remove oil stains, and then use a sandblasting machine to sandblast the substrate. The sand type used in the sandblasting machine is white corundum sand, the sandblasting pressure is 0.5 MPa, the sandblasting distance is 100 mm, the sandblasting angle is 75°, and the sandblasting time is 3 s; S2. The substrate surface treated in step S1 is sprayed with NiCrAlY by an atmospheric plasma spraying system to obtain a base layer with a thickness of 80 μm, and then the plasma sprayed ceramic powder prepared in Preparation Example 1.1 is sprayed to obtain a ceramic layer with a thickness of 180 μm, wherein the atmospheric plasma spraying system uses Ar as the main gas and carrier gas, H2 as the auxiliary gas, the gas flow rate during spraying is 30 L / min, the powder feeding rate is 10 g / min, the spraying distance is 100 mm, and the spraying angle is 30°; S3. A mixture of YJ7050-13 silicone resin and sodium fluorosilicate in a weight ratio of 5:1 is used as a sealing agent to seal the substrate treated in step S2 to obtain a ceramic composite coating, wherein the specific operation of the sealing treatment is: the substrate is completely immersed in the sealing agent for 30 minutes, then taken out and dried at a temperature of 115°C for 15 minutes.

[0043] Example 1.2 A method for preparing a ceramic composite coating comprises the following steps: S1. Use a grinding wheel to grind away dirt on the surface of the substrate, then wipe it with anhydrous ethanol and chamfer the edge area of ​​the substrate by 0.5 mm, then completely immerse the substrate in an acetone solution for ultrasonic cleaning for 15 minutes to remove oil stains, and then use a sandblasting machine to sandblast the substrate. The sand type used in the sandblasting machine is white corundum sand, the sandblasting pressure is 0.6 MPa, the sandblasting distance is 120 mm, the sandblasting angle is 80°, and the sandblasting time is 3 seconds; S2. The substrate surface treated in step S1 is sprayed with NiCrAlY by an atmospheric plasma spraying system to obtain a base layer with a thickness of 100 μm, and then the plasma sprayed ceramic powder prepared in Preparation Example 1.1 is sprayed to obtain a ceramic layer with a thickness of 220 μm, wherein the atmospheric plasma spraying system uses Ar as the main gas and carrier gas, H2 as the auxiliary gas, the gas flow rate during spraying is 30 L / min, the powder feeding rate is 10 g / min, the spraying distance is 100 mm, and the spraying angle is 30°; S3. A mixture of YJ7050-13 silicone resin and sodium fluorosilicate in a weight ratio of 5:1 is used as a sealing agent to seal the substrate treated in step S2 to obtain a ceramic composite coating, wherein the specific operation of the sealing treatment is: the substrate is completely immersed in the sealing agent for 30 minutes, then taken out and dried at a temperature of 115°C for 15 minutes.

[0044] Examples 2.1-2.3 A method for preparing a ceramic composite coating is different from Example 1.2 in that: in step S2, the plasma sprayed ceramic powders are the plasma sprayed ceramic powders prepared in Preparation Examples 1.2-1.4 respectively, and the rest are the same as Example 1.2.

[0045] Examples 3.1-3.2 A method for preparing a ceramic composite coating is different from that of Example 1.2 in that: in step S2, the plasma sprayed ceramic powders are the plasma sprayed ceramic powders prepared in Preparation Examples 2.1-2.2, and the rest are the same as those of Example 1.2.

[0046] Example 4.1 A method for preparing a ceramic composite coating, which is different from Example 1.2 in that: in step S2, the gas flow rate during spraying is 35 L / min, and the rest is the same as Example 1.2.

[0047] Example 4.2 A method for preparing a ceramic composite coating is different from that of Example 1.2 in that: in step S2, the gas flow rate during spraying is 40 L / min, and the rest is the same as that of Example 1.2.

[0048] Example 5.1 A method for preparing a ceramic composite coating is different from that of Example 1.2 in that: in step S2, the powder feeding rate during spraying is 15 g / min, and the rest is the same as that of Example 1.2.

[0049] Example 5.2 A method for preparing a ceramic composite coating is different from that of Example 1.2 in that: in step S2, the powder feeding rate during spraying is 20 g / min, and the rest is the same as that of Example 1.2.

[0050] Example 6.1 A method for preparing a ceramic composite coating is different from that of Example 1.2 in that: in step S2, the spraying distance is 110 mm, and the rest is the same as that of Example 1.2.

[0051] Example 6.2 A method for preparing a ceramic composite coating, which is different from Example 1.2 in that: in step S2, the spraying distance is 120 mm, and the rest is the same as Example 1.2.

[0052] Example 7.1 A method for preparing a ceramic composite coating is different from that of Example 1.2 in that: in step S2, the spraying angle is 45°, and the rest is the same as that of Example 1.2.

[0053] Example 7.2 A method for preparing a ceramic composite coating is different from that of Example 1.2 in that: in step S2, the spraying angle is 90°, and the rest is the same as that of Example 1.2.

[0054] Examples 8.1-8.3 A method for preparing a ceramic composite coating, which differs from Example 1.2 in that: in step S3, the sealing agent in the sealing treatment is the sealing agent prepared in Preparation Examples 3.1-3.3, and the specific operation of the sealing treatment is to completely immerse the substrate in the sealing agent, immerse for 10 seconds and then pull it up at a uniform speed, repeat 3 times, keep it warm at 300°C for 60 minutes, and then cool and take it out.

[0055] Comparative Examples 1.1-1.2 The difference from Example 1.2 is that in step S2, the plasma spraying ceramic powders prepared in Comparative Preparation Examples 1.1-1.2 are respectively used, and the rest are the same as Example 1.2.

[0056] Comparative Examples 2.1-2.2 The difference from Example 1.2 is that in step S2, the plasma spraying ceramic powders prepared in Comparative Preparation Examples 2.1-2.2 are respectively used, and the rest are the same as Example 1.2.

[0057] Performance Testing 1. The porosity of the cross-section of the coatings prepared in the above embodiments and comparative examples was calculated using Image Pro Plus software. The results are shown in Table 1. 2. Hardness measurement was performed on the cross section of the coating obtained in the above embodiment and comparative example. In order to ensure the smoothness of the cross section, the cross section of the coating was polished with sandpaper. The hardness was measured in the smooth area using a micro Vickers hardness tester (HV-1000A). During the measurement, the loading load was set to 200 g and the load was maintained for 10 seconds. In order to ensure the accuracy of the results, 5 points were randomly selected on the cross section for hardness measurement, and the average value of the results was taken as the hardness value of the cross section. The results are shown in Table 1. 3. The corrosion resistance of the coatings obtained in the above embodiments and comparative examples was electrochemically tested in 3.5wt% NaCl solution and 5wt% HCl solution simulating seawater media, respectively, using a CS350H electrochemical workstation; the tested sample was welded to a copper wire and then sealed and used as a working electrode, with only the coating surface left at the bottom, edge and connection with the copper wire of the sealed sample, an Ag / AgCl electrode was used as a reference electrode, and a metal platinum sheet was used as a counter electrode. During the test, the initial potential was -1.5V, the termination potential was +2V, and the scanning speed was 5mV / s. The sample was immersed in a corrosive solution to allow the open circuit potential to reach a stable test, and then a polarization test was performed. After the test, a polarization curve was drawn by plotting the change of corrosion potential and corrosion current over time. According to the Tafel extrapolation method, the corrosion potential was calculated at the intersection of the linear fit of the polarization curve. The results are shown in Table 1.

[0058] Table 1 Performance test results Data Analysis: As can be seen from Table 1, the porosity of the coatings prepared in Examples 1.1-7.2 of the present application is less than 2.35%, and the lowest can reach 0.84%. The hardness is greater than 950HV, and the highest can reach 998HV. During electrochemical corrosion in 3.5wt% NaCl solution, the corrosion point is -0.7994 to -0.9710V, and during electrochemical corrosion in 5wt% HCl solution, the corrosion point is -0.3612 to -0.4640V. The test data show that the coatings prepared in Examples 1.1-7.2 of the present application have lower porosity, higher density, and stronger corrosion resistance.

[0059] Among them, by comparing the data of Example 1.2 and Examples 2.1-2.3, it can be seen that when the weight ratio of nano-Al2O3 powder, nano-TiO2 powder, nano-CeO2 powder and nano-YSZ powder is 82:10:2:6, the porosity of the coating reaches the lowest, the hardness reaches the highest, and the corrosion resistance reaches the strongest.

[0060] By comparing the data of Example 1.2 and Examples 3.1-3.2, it can be seen that when the weight ratio of nano powder to silicate glass powder is 10:2, the porosity of the coating reaches the lowest, the hardness reaches the highest, and the corrosion resistance reaches the strongest.

[0061] By comparing the data of Example 1.2 and Example 4.1-7.2, it can be seen that the change of process parameters during spraying will affect the porosity, hardness and corrosion resistance of the coating. Taking into account the effects of various parameters, when the spraying gas flow rate is 30L / min, the powder feeding rate is 20g / min, the spraying distance is 100mm, and the spraying angle is 90°, the coating has the lowest porosity, the highest hardness, and the strongest corrosion resistance.

[0062] The difference between Example 8.1-8.3 and Example 1.2 is that the sealing agent used in the sealing treatment is different. It can be seen from the data that compared with the use of only organic sealing agents, the coating prepared by using organic-inorganic hybrid sealing agents has lower porosity, higher hardness and stronger corrosion resistance. In addition, after high-temperature oxidation experiments at 1300°C on Example 1.2 and Example 8.1-8.3, it was found that the oxidation weight gain rate of Example 1.2 was 0.0118%, while the oxidation weight gain rate of Example 8.1 was only 0.0052%, the oxidation weight gain rate of Example 8.2 was only 0.0071%, and the oxidation weight gain rate of Example 8.3 was only 0.072%, which shows that the use of organic silicon base material and ZrO2 coated SiC-CeO2 sealing particles mixed as sealing agents can significantly improve the high-temperature oxidation resistance of the coating, and as the amount of CeO2 added increases, the high-temperature oxidation resistance of the coating is enhanced.

[0063] The difference between Comparative Example 1.1 and Example 1.2 is that no nano YSZ powder is added. As can be seen from Table 1, the porosity of Comparative Example 1.1 is 4.36%, the hardness is 837 HV, the corrosion point is -1.0314 V during electrochemical corrosion in 3.5 wt % NaCl solution, and the corrosion point is -0.4918 V during electrochemical corrosion in 5 wt % HCl solution. The test data show that the addition of nano YSZ powder in the present application can significantly reduce the porosity of the coating, improve the corrosion resistance of the coating, and extend the service life of the coating.

[0064] By comparing the data of Example 1.2, Comparative Example 1.2 and Examples 2.1-2.3, it can be seen that the amount of nano YSZ powder added should not be too much. If the amount added is too much, the porosity of the coating will increase and the corrosion resistance of the coating will be reduced.

[0065] The difference between Comparative Example 2.1 and Example 1.2 is that no nano YSZ powder is added. As can be seen from Table 1, the porosity of Comparative Example 2.1 is 2.13%, the hardness is 967HV, the corrosion point is -0.9388V during electrochemical corrosion in 3.5wt% NaCl solution, and the corrosion point is -0.4527V during electrochemical corrosion in 5wt% HCl solution. The test data show that the addition of silicate glass powder in this application can significantly reduce the porosity of the coating, improve the corrosion resistance of the coating, and extend the service life of the coating.

[0066] By comparing the data of Example 1.2, Comparative Example 2.2 and Examples 3.1-3.2, it can be seen that the amount of silicate glass powder added should not be too much. If the amount added is too much, the porosity of the coating will increase and the corrosion resistance of the coating will be reduced.

[0067] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A plasma sprayed ceramic powder, characterized in that: The raw materials used include the following components in parts by weight: 100 parts of nano powder and 10-30 parts of silicate glass powder; the nano powder includes nano Al2O3 powder, nano TiO2 powder, nano CeO2 powder and nano YSZ powder in a weight ratio of (80-86):10:2:(2-8).

2. The plasma spraying ceramic powder according to claim 1, characterized in that: The nano powder includes nano Al2O3 powder, nano TiO2 powder, nano CeO2 powder and nano YSZ powder in a weight ratio of 82:10:2:

6.

3. The plasma spraying ceramic powder according to claim 1, characterized in that: The plasma sprayed ceramic powder has an average particle size of 52.34-82.35 μm, a fluidity of 10.73-11.87 g / min, and a bulk density of 0.52-0.56 g / cm 3 , tap density is 0.87-0.90g / cm 3 .

4. A method for preparing a ceramic composite coating, characterized in that: The following steps are involved: S1. Degreasing and cleaning the substrate surface and pre-treating it by sandblasting; S2. Spraying a bonding layer on the surface of the substrate treated in step S1, and then spraying the plasma sprayed ceramic powder according to any one of claims 1-3; S3. Use a sealing agent to seal the substrate treated in step S2 to obtain a ceramic composite coating.

5. The method for preparing a ceramic composite coating according to claim 4, characterized in that: In the step S1, the sandblasting pretreatment has a sandblasting pressure of 0.5-0.6 MPa, a sandblasting distance of 100-120 mm, and a sandblasting angle of 75-80°.

6. The method for preparing a ceramic composite coating according to claim 4, characterized in that: In the step S2, the gas flow rate during spraying is 30-40 L / min, the powder feeding rate is 10-20 g / min, the spraying distance is 100-120 mm, and the spraying angle is 30-90°.

7. The method for preparing a ceramic composite coating according to claim 6, characterized in that: The gas includes Ar and H2, with Ar serving as a main gas and a carrier gas, and H2 serving as an auxiliary gas.

8. The method for preparing a ceramic composite coating according to claim 4, characterized in that: The sealing agent in step S3 includes an organic silicon base material and ZrO2 coated SiC-CeO2 sealing particles in a weight ratio of (1.8-2.2):

1.

9. The method for preparing a ceramic composite coating according to claim 8, characterized in that: The weight ratio of SiC to CeO2 in the ZrO2-coated SiC-CeO2 sealing particles is (98-99.5): (0.5-2).

10. A ceramic composite coating prepared by the method for preparing a ceramic composite coating according to claim 4.

Citation Information

Patent Citations

  • Granules of a brittle material for vacuum granule injection at room temperature, and method for forming a coating film using same

    CN103501888A

  • Method for preparing ceramic coating lining of mud pump cylinder sleeve

    CN104087890A

  • CYSZ thermal barrier coating prepared through plasma thermal spraying method and preparing method

    CN106435446A

  • Glass powder for modifying plasma spray ceramic coating, preparing method and application thereof

    CN107056074A

  • POWDER COMPRISING ZIRCONIA GRANULES

    FR2954761A1

Cited By

  • Grid section for roasting trolley and preparation method thereof

    CN119710520A

  • Ceramic powder and compact insulating coating

    CN122446107A